Evaluation of DNA and RNA quality from archival formalin‐fixed paraffin‐embedded tissue for next‐generation sequencing – Retrospective study in Japanese single institution. Issue 9 (15th June 2020) - Fujii, Tomomi; Uchiyama, Tomoko; Matsuoka, Minami; Myojin, Tomoya; Sugimoto, Sumire; Nitta, Yuji; Okabe, Fumi; Sugimoto, Aya; Sekita‐Hatakeyama, Yoko; Morita, Kohei; Itami, Hiroe; Hatakeyama, Kinta; et al.
Abstract : Genetic analysis on formalin‐fixed paraffin‐embedded (FFPE) tissue specimens has become a mainstream method, from conventional direct sequencing to comprehensive analysis using next‐generation sequencing (NGS). In this study, we evaluated the quality of DNA and RNA extracted from FFPE sections, derived from surgical specimens of different tumor types. Electrophoresis was performed using a 4200 TapeStation to evaluate DNA and RNA fragmentation. DNA Ct values were higher and significantly increased over a period of 4 years compared with those from cell lines or frozen tissues. The RNA integrity number equivalent (RIN) ranged from 1 to 4.1 and DV200 ranged from 7.3 to 81%. Twelve of the 108 cases were analyzed by NGS using the AmpliSeq Cancer HotSpot Panel v2 on a Miniseq system. A sufficient number of reads and coverage were obtained in all cases. Our results revealed that NGS analysis was sufficient for FFPE‐derived DNA within 4 years of preservation. Conversely, approximately 20% of the RNA derived from FFPE within 4 years from the collection could be inappropriate for gene analysis based on RIN and DV200. It was suggested that FFPE would be adequate for genetic analysis, although it is desirable to store frozen specimens for the tumor tissues to be subjected to genetic analysis.